Lumpy investment in sticky information general equilibrium - Fabio Verona (Bank of Finland, 2013)
In this paper, I introduce lumpy micro-level capital adjustment into a sticky information general equilibrium model. Lumpy adjustment arises because of inattentiveness in capital investment decisions instead of the more common assumption of non-convex adjustment costs. The model features inattentiveness as the only source of stickiness. I find that the model with lumpy investment yields business cycle dynamics which differ substantially from those of an otherwise identical model with frictionless investment and are much more consistent with the empirical evidence. These results therefore strengthen the case in favour of the relevance of microeconomic investment lumpiness for the business cycle.
URN:NBN:fi:bof-20140807433
Keywords: D83; E10; E22; E32; 330; sticky information; general equilibrium; lumpy investment; business cycle